LEGAL PROTECTION FOR THE RIGHTS OF PRISONERS IN DIVORCE CASES IN THE RELIGIOUS COURTS IN INDONESIA - Darsono; Ellydar Chaidir; Abd Thalib; Efendi Ibnu Susilo (International Conference On Law And Social Sciences, 2024)
This paper explores the legal protection available for prisoners in divorce cases adjudicated by religious courts in Indonesia. It examines the unique challenges faced by incarcerated individuals seeking divorce and the extent to which Indonesian religious courts accommodate their rights and needs. By analyzing relevant laws, judicial practices, and case studies, the study highlights gaps and inconsistencies in the current legal framework. It also evaluates the impact of these gaps on the fairness and accessibility of divorce proceedings for prisoners. The findings aim to provide recommendations for improving legal protections and ensuring that prisoners' rights are upheld within the context of Indonesian religious law.